PELATIHAN DAN PENDAMPINGAN TATA KELOLA KEUANGAN BUM DESA DI KABUPATEN LOMBOK BARAT - Iman Waskito; Jumaidi, Lalu Takdir; Fikri, M. Ali; Nirmala, Yeni (Universitas Mataram, 2024)
Financial reports are an instrument for measuring the performance of every business entity, including BUM Desa. Without financial reports, the performance of BUM Desa cannot be assessed for its development, so that every inclusion of Village funds in it is very risky. The low capacity of BUM Desa human resources is the cause of the absence of financial reports. Therefore, strengthening BUM Desa human resources is needed to support the realization of financial reports. This community service activity aims to strengthen the capacity of BUM Desa human resources to prepare financial reports. There are 24 BUM Desa selected as participants in this community service activity. The selection criteria are that they are registered with the P3MD of West Lombok Regency, have business activities, and represent each sub-district. Until the completion of this community service activity report, there are still mentoring activities that continue to be provided by the community service team. Because it is realized that the preparation of this financial report can be sustainable, which of course does not rule out the possibility that there are problems whose resolution requires mentoring.